CEO Greed, Corporate Governance, and CSR Performance: Asian Evidence - Saif Ur Rehman; Yacoub Haider Hamdan (Administrative Sciences, 2023)
In this study, we examined the association between CEO greed and corporate social responsibility (CSR) performance with a particular emphasis on the curtailing role of corporate governance. We found that CEO greed has a negative effect on CSR, since an uncontrolled pursuit of personal gain typically reveals myopic behavior and the foregoing of investment in CSR by a greedy CEO. Additionally, we found that CEO compensation in the form of large bonuses, support, and restricted stocks options weakened the link between CEO greed and CSR. Concerning the power dynamics amongst CEOs (CEO duality and tenure), we found that CEO duality moderates the negative relation between CEO greed and CSR. We also explored the curtailing role of corporate governance (proxies represented by board gender diversity and board independence) in the association between CEO greed and CSR. Our findings show that gender diversity curtails the negative effect of CEO greed on CSR once it reaches critical mass on the corporate board. Gender critical mass also curtails the negative impact of CEO greed on CSR, even if the CEO exercises duality. Our findings have empirical and practical implications. This study contributes to the existing literature by exploring the relationship between CEO greed and CSR in Asia, a region not renowned for CSR performance. This study also provides evidence for the curtailing role of compensation and governance factors in the negative relationship between CEO greed and CSR.